Comparison of ticagrelor with clopidogrel in patients with a planned invasive strategy for acute coronary syndromes (PLATO): a randomised double-blind study - Cannon, Christopher P.; Harrington, Robert A; James, Stefan; Ardissino, Diego; Becker, Richard C; Emanuelsson, Håkan; Husted, Steen; Katus, Hugo; Keltai, Matyas; Khurmi, Nardev S; Kontny, Frederic; Lewis, Basil S; et al. (The lancet, 2010)
Background - Variation in and irreversibility of platelet inhibition with clopidogrel has led to controversy about its optimum dose and timing of administration in patients with acute coronary syndromes. We compared ticagrelor, a more potent reversible P2Y12 inhibitor with clopidogrel in such patients. - Methods - At randomisation, an invasive strategy was planned for 13 408 (72·0%) of 18 624 patients hospitalised for acute coronary syndromes (with or without ST elevation). In a double-blind, double-dummy study, patients were randomly assigned in a one-to-one ratio to ticagrelor and placebo (180 mg loading dose followed by 90 mg twice a day), or to clopidogrel and placebo (300-600 mg loading dose or continuation with maintenance dose followed by 75 mg per day) for 6-12 months. All patients were given aspirin. The primary composite endpoint was cardiovascular death, myocardial infarction, or stroke. Analyses were by intention to treat. This trial is registered with ClinicalTrials.gov, number NCT00391872. - Findings - 6732 patients were assigned to ticagrelor and 6676 to clopidogrel. The primary composite endpoint occurred in fewer patients in the ticagrelor group than in the clopidogrel group (569 [event rate at 360 days 9·0%] vs 668 [10·7%], hazard ratio 0·84, 95% CI 0·75-0·94; p=0·0025). There was no difference between clopidogrel and ticagrelor groups in the rates of total major bleeding (691 [11·6%] vs 689 [11·5%], 0·99 [0·89-1·10]; p=0·8803) or severe bleeding, as defined according to the Global Use of Strategies To Open occluded coronary arteries, (198 [3·2%] vs 185 [2·9%], 0·91 [0·74-1·12]; p=0·3785). - Interpretation - Ticagrelor seems to be a better option than clopidogrel for patients with acute coronary syndromes for whom an early invasive strategy is planned. - Funding - AstraZeneca.